(untitled) - Jenkins, Lee. (Thousand Oaks, 2016)
This book creates a whole picture approach to school improvement while shunning the current top down model in favor of a school-led plan. The approach not only increases school performances, but values the school-level leadership and instructional facult
Keywords: Kế hoạch giáo dục,Tổ chức và quản lý trường học,Educational planning,School management and organization; Hoa Kỳ,United States,United States.,United States